Determinants of infarction patterns in posterior cerebral circulation - Taha K Alloush; Ramez R Moustafa; Mohamed M Fouad; Ahmed H. T Badr Ahmed (Journal of Medicine in Scientific Research, 2019)
Background Ischemic stroke is defined as focal or global neurological dysfunction lasting longer than 24 h or leading to death that is caused by vascular insult, either stricture or occlusion of a specific vascular territory. Aim of the study This study aimed to determine the relationship between different risk factors and different infarction patterns in posterior circulation such single small lacunar lesion, single large lesion, and multiple scattered lesions. Patients and methods This study included 60 patients recruited from the stroke unit of Ain Shams University and El Sahel Teaching Hospitals during the period from April to October 2018 with the diagnosis of posterior circulation ischemic stroke. The study population was divided into three groups according to the infarction pattern. Infarction patterns were categorized into a single small lacunar lesion (20 patients) (group I), a single large lesion (20 patients) (group II), and multiple scattered lesions (20 patients) (group III). Results There was no significant difference between the three groups in the presence of vascular risk factors such as hypertension (P = 0.153), diabetes (P = 0.317), dyslipidemia (P = 0.420), presence of cardiac diseases (P = 0.180), and smoking (P = 0.931). The only significant difference in terms of vascular risk factors was atrial fibrillation (AF). AF was present in six patients in group II and six patients in group III, and not present in group I patients (P = 0.024). Conclusion Different vascular risk factors such as hypertension, diabetes, dyslipidemia, and smoking are present in all infarction patterns of posterior cerebral circulation, either single or multiple infarctions, and there were no significant differences in the presence of these vascular risk factors in relation to the type of the vascular lesion. AF and significant vertebrobasilar stenosis were mostly associated with large and multiple infarct lesion patterns. Small-vessel disease was the most common stroke etiology for a single small lacunar lesion, whereas large artery atherosclerosis was mostly present in a single large lesion and multiple lesions. Strict control of vascular risk factors is highly recommended in all infarction patterns of posterior circulation.